Republic of Madagascar : Poverty Reduction Strategy Paper; Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2009)
This Joint Staff Advisory Note provides feedback from the World Bank and IMF staff on the first and second progress reports on the Madagascar Action Plan (MAP)-the poverty reduction and growth strategy for 2007-12. Progress on governance has been reported with improvements in the functioning of the national anticorruption agency (BIANCO), the establishment of a financial intelligence unit, and improved national security indicators. To further improve transparency, the government will need to make an effort to secure property rights through the judicial system or alternative conflict-resolution mechanisms.